Drivers and barriers to Industrial Revolution 5.0 readiness: A comprehensive review of key factors - Ghazali, Ihwan; Wan Mahmood, Wan Hasrulnizzam; Tanjung, Tia; Herawan, Safarudin Gazali (Green Technologies and Sustainability, 2025)
As industries navigate the transition toward Industrial Revolution 5.0, understanding the key drivers and barriers to readiness becomes crucial. This study conducts a comprehensive literature review to uncover the critical factors shaping IR 5.0 adoption. The findings highlight that technological advancements, workforce upskilling, and supportive policies serve as primary drivers, accelerating the shift toward human-centric and sustainable industrial ecosystems. Conversely, resistance to change, financial constraints, and lack of awareness emerge as significant barriers, impeding progress. To bridge these gaps, this study emphasizes the need for strategic investments in advanced technologies, targeted workforce development programs, and robust policy frameworks. By offering a structured analysis of the enablers and inhibitors of IR 5.0 adoption, this research provides valuable insights for industry leaders, policymakers, and academics, fostering sustainable growth and innovation in an era of rapid technological evolution.